Estrategias de marketing digital en la empresa de todo repuestos automotrices de la ciudad de Guayaquil periodo 2023. - Gastesi Reyes, Mitzi Marilyn (2024)
Digital marketing tactics in the auto parts company in Guayaquil for the year 2023 must adjust to technological trends and the tastes of the local customer. It is essential to use platforms such as Facebook and Instagram, since they are the most frequented among users in Ecuador. Through the constant dissemination of automotive products, services and recommendations, the company has the possibility of establishing a direct interaction with its consumers. Additionally, specific advertising campaigns on these platforms will make it possible to reach a specific audience that is interested in vehicle parts and services. For an auto parts company in Guayaquil, implementing clearly established digital marketing strategies, such as a robust online presence, an emphasis on educational content and the use of analytical tools, can increase its visibility, attract more customers and, ultimately, increase sales.